Dampak Pembangunan Waterfront Pontianak CityTerhadap Perubahan Aspek Kehidupan Masyarakat Sekitar Tepian Sungai Kapuas - Suryanto, Bangun Eddi; Devi, Friska (Tanjungpura University, 2020)
The purpose of the study with the title the impact of Pontianak City waterfront development on changes in aspects of community life around the banks of the Kapuas river, by taking the issue of how the economic situation of the community around before and after the construction of Waterfront Pontianak City and how the impact of the development of Pontianak City waterfront on aspects of community life around the banks of the river Kapuas. This research method is a descriptive qualitative approach, using interview and observation techniques. The results showed that the changes that occurred after the development of Waterfront Pontianak City experienced positive and negative impacts. Where these changes occur in economic aspects and social welfare. Changes in the economic aspects, namely they feel the income they get increased from before this development. But for the sake of the construction of the Waterfront Pontianak City, the government demolished the houses of residents around the banks of the Kapuas river. So this causes the pros and cons of the community because the community feels that the compensation given by the government is not what they expected.